2021
DOI: 10.25122/jml-2019-0135
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to early mobilization of intensive care unit patients by nurses in hospitals affiliated to Jundishapur University of Medical Sciences of Ahvaz in 2019

Abstract: Early mobilization (EM) of patients in the intensive care unit (ICU) is a safe, feasible, and beneficial approach. However, the implementation of EM as a part of routine clinical care can be challenging. As a result, the present study aimed to identify the potential barriers to EM of ICU patients. The statistical population of this descriptive-analytical study included 107 critical care nurses working in hospitals affiliated with the Jundishapur University of Medical Sciences of Ahvaz. The participants were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…Early mobilization proved to be effective and safe in many studies, despite the evidence , many surveys and studies of early mobilization practice have shown limited penetration, particularly in patients undergoing MV, and EM is not implemented in the daily practice in many ICUs [16].Knowledge of environmental barriers and personal experiences is of utmost importance for innovating and implementing a new practice [13]. Furthermore, studying attitudes of ICU workers especially nurses, variation in ICU structure, patient and family culture may be most associated with (and hence most favorable for) implementing EM practice [17]. The present study aimed to assess barriers perceived by nurses in the 3 intensive care units (ICUs) at Beni-Suef University Therefore, special care should be provided to ensure patient safety [18].…”
Section: Resultsmentioning
confidence: 99%
“…Early mobilization proved to be effective and safe in many studies, despite the evidence , many surveys and studies of early mobilization practice have shown limited penetration, particularly in patients undergoing MV, and EM is not implemented in the daily practice in many ICUs [16].Knowledge of environmental barriers and personal experiences is of utmost importance for innovating and implementing a new practice [13]. Furthermore, studying attitudes of ICU workers especially nurses, variation in ICU structure, patient and family culture may be most associated with (and hence most favorable for) implementing EM practice [17]. The present study aimed to assess barriers perceived by nurses in the 3 intensive care units (ICUs) at Beni-Suef University Therefore, special care should be provided to ensure patient safety [18].…”
Section: Resultsmentioning
confidence: 99%
“…Nas Unidades de Terapia Intensiva (UTI) diversos procedimentos são conduzidos diariamente para o manejo clínico adequado, seguro e eficaz de pacientes com doenças graves 1 . O contexto que envolve o cuidado em UTI pode resultar em pacientes com baixo nível de mobilidade, em especial, aqueles em ventilação mecânica, prolongando o tempo de internação hospitalar [2][3][4] .…”
Section: Introductionunclassified
“…Babazadeh et al 1 evidenciam que o baixo (re) conhecimento de barreiras para MP por parte de profissionais da saúde pode levar a uma lacuna no desempenho da conduta. Alguns estudos 1,9 já buscaram descrever sobre barreiras para MP e destacam a baixa proporção de pessoal de enfermagem e fisioterapia nas unidades, ausência de treinamento, linhas e tubos arteriais, profundo grau de sedação, recusa informada etc. Porém até o presente momento nenhum estudo foi identificado com amostra de fisioterapeutas intensivistas com atuação no contexto de saúde do Ceará/Brasil.…”
Section: Introductionunclassified
“…Critically ill adult patients may present with various complications from hospitalization in an intensive care unit (ICU) stay [1,2]. Being on mechanical ventilation, sedation, neuromuscular blockade, and the mobility restrictions imposed by the context of critical illness, as well as barriers derived from invasive devices in critically ill patients [3][4][5], create an environment that can facilitate cognitive [6] and neuromusculoskeletal complications [7], among others.…”
Section: Introductionmentioning
confidence: 99%